Dikotomi Ilmu Pengetahuan Dalam Islam Perspektif al-Ghazali - Rizal, Syamsul; Nasir, Mohd; Pratiwi, Indah (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
This article examines the dichotomy of knowledge in Islam from al-Ghazali's perspective. The emergence of al-Ghazali amidst the setbacks and divisions that occurred in the Muslim community due to differences in thought and understanding has had a major impact on the unity of the Muslim community. Al-Ghazali has given birth to new thoughts and, at the same time, created a scientific dichotomy among Muslims. Al-Ghazali has compartmentalized general knowledge with religious knowledge, thus creating a scientific dichotomy that never previously existed among Muslims. This type of library research uses a qualitative approach by examining various related references related to the theme of the article. This paper has produced several important findings. First, al-Ghazali's response to the crisis that occurred in society. Second, the scientific paradigm during al-Ghazali's time and before. Third, al-Ghazali's scientific paradigm and its influence on western and Islamic science; and fourth, al-Ghazali's influence on the dichotomy of science in the Islamic intellectual tradition. These four findings can reveal the great role of al-Ghazali's scientific paradigm and the influence of its dichotomy on the development of Islamic scientific civilization.